2020
DOI: 10.31661/gmj.v9i0.1829
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Excitatory Effects of MicroRNA-30 in the Self-Renewal and Differentiation Process of Neonatal Mouse Spermatogonial Stem Cells

Abstract: Background: Spermatogonial stem cells (SSCs) are considered as special stem cells since they have the ability of self-renewal, differentiation, and transferring genetic information to the next generation. Also, they considered as vital players in initiating and preserving spermatogenesis. The fate decisions of SSCs are mediated by intrinsic and extrinsic factors, among which microRNAs (miRNAs) are one of the most essential factors in spermatogenesis among endogenous regulators. However, the mechanisms by which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…A considerable point in this regard is that although these markers have been introduced by other researchers as possible markers for SSC identity, no exclusive marker has yet been recommended for purification of SSCs. Other markers such as Plzf, α6, β1, and GFR α1 have also been used for purification of SSCs in the literature [ 31 , 32 , 38 ]. In this study, the high percentage of expression for these markers confirmed that the collected cells were undifferentiated since SSCs first appear at 3–6 days postpartum in mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A considerable point in this regard is that although these markers have been introduced by other researchers as possible markers for SSC identity, no exclusive marker has yet been recommended for purification of SSCs. Other markers such as Plzf, α6, β1, and GFR α1 have also been used for purification of SSCs in the literature [ 31 , 32 , 38 ]. In this study, the high percentage of expression for these markers confirmed that the collected cells were undifferentiated since SSCs first appear at 3–6 days postpartum in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Melting curve analysis was used to identify the non-specific real-time PCR products. U6 snRNA was selected as an internal control gene and the miR-30a-5p expression was calculated through 2-∆∆CT method [ 31 , 32 ]. Quantitative real-time PCR was done in triplicate for each sample.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study, the proliferation or undifferentiation marker ID4 was considerably upregulated in SSCs treated with an miR-30 mimic, suggesting that miR-30 regulates the self-renewal capability of SSCs ( 83 ). miR-31-5p inhibits proliferation and DNA synthesis and increases early and late apoptosis of human SSCs by targeting JAZF1 and cyclin A2 ( 84 ).…”
Section: Mechanism Of Mirna Involved In Spermatogenesismentioning
confidence: 91%
“…All the inventors of different countries representing the particular invention, along with the patent number, title of invention, granting country, and authority, have been listed in this table 1. The chemical composition of Ajwain oil with different major constituents including thymol 28 , γ-terpinene, and p-cymene 2,29 carvone, limonene, and dillapiole and carvacrol 2 . Fruit extract showed antispasmodic and antihypertensive effects by preventing contraction caused by K+.…”
Section: Introductionmentioning
confidence: 99%